2021
DOI: 10.1177/0963721420980753
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Imaginative Mind: Charting New Paths Forward

Abstract: The fields of psychology and neuroscience are in the midst of an explosion of research aimed at illuminating the human imagination—the ability to form thoughts and mental images that stretch beyond what is currently available to the senses. Imaginative thought is proving to be remarkably diverse, capturing the capacity to recall past experiences, consider what lies ahead, and understand other people’s minds, in addition to other forms of creative and spontaneous thinking. In the first part of this article, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 40 publications
16
50
0
Order By: Relevance
“…Consistent with the idea that past and future thinking rely on a common set of cognitive processes and underlying brain network [15,16,17,18,19] we found that APOE4 carriers also showed a reduction in episodic (i.e., internal), but not non-episodic (i.e., external), detail while imagining future personal events. Like the memory results, the magnitude of this APOE4 effect for future thinking was moderate (d = .46).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Consistent with the idea that past and future thinking rely on a common set of cognitive processes and underlying brain network [15,16,17,18,19] we found that APOE4 carriers also showed a reduction in episodic (i.e., internal), but not non-episodic (i.e., external), detail while imagining future personal events. Like the memory results, the magnitude of this APOE4 effect for future thinking was moderate (d = .46).…”
Section: Discussionsupporting
confidence: 86%
“…In light of the potential significance of reduced episodic detail to detecting the cognitive impact of higher Alzheimer's disease risk in clinically normal older adults, we aimed to replicate and extend our earlier findings in the present study by examining future-oriented autobiographical thinking. Some theories propose that the brain mentally constructs past and future events using similar cognitive processes, and an overlapping brain network [15,16,17,18,19]. However, whether APOE4 status, or any Alzheimer's disease risk factor for that matter, impacts future-oriented episodic detail generation in clinically normal older adults is not known.…”
Section: Future Episodic Detail Generation Among Apoe4 Carriersmentioning
confidence: 99%
“…Collectively, regions of overlap are purported to belong to the so-called “default network,” a brain system thought to support the emergence of thoughts/attention decoupled from immediate sensory input, which humans tend to “default to” during passive rest periods (Binder et al, 1999; Buckner et al, 2008; Raffaelli et al, 2020; Raichle et al, 2001; Smallwood et al, 2012). Critically, the default network may also support our ability to schematize, understand, and make meaning out of a wide range of perceptual stimuli, memories, and socioemotional experiences (Andrews-Hanna & Grilli, 2021; Koban et al, 2021; Roy et al, 2012; Satpute & Lindquist, 2019; Woo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…He concluded that if we want to have good ideas, we must have lots of ideas and learn to throw away the bad ones (as cited in Kirwan, 2017; see also Lortie, 2017). Although much knowledge exists on individuals’ creative potential on a between-person level as the potential to solve open problems (e.g., Barbot, 2018; Fink & Benedek, 2014; Runco & Acar, 2012), research has largely neglected the moment-to-moment fluctuations of creative ideation performance (i.e., the momentary realization of one’s creative potential; but see, e.g., Andrews-Hanna & Grilli, 2021; Barbot, 2019, 2022; Corazza et al, 2022; Guilford, 1950). The well-known serial order effect in idea generation, which describes an increase in the average originality of ideas with time on the task, constitutes one prominent exception of this strong between-person focus (Beaty & Silvia, 2012; Christensen et al, 1957).…”
Section: Benefits Of An Ecological Momentary Assessment (Ema)mentioning
confidence: 99%